Cerebral pontine infarctions during pregnancy - A case report and review of the literature - Jenna Kaye Wildman; Bassam H. Rimawi (Elsevier, 2019)
Cerebrovascular disease is not uncommon during pregnancy as a result of either venous or arterial occlusion, or a hemorrhagic event, resulting in ischemia. Pregnancy may alter the prognosis of these neurologic disorders, with increased risks of morbidity and mortality for the mother and the developing fetus. Etiologies of stroke during pregnancy and the postpartum period include preeclampsia, eclampsia, HELLP syndrome, posterior reversible encephalopathy syndrome (PRES), amniotic fluid embolism, postpartum angiopathy, postpartum cardiomyopathy, thrombotic thrombocytopenic purpura (TTP), hemolytic uremic syndrome (HUS), cerebral venous thrombosis, CNS infections, and maternal thrombophilia.Essentially any of the vessels in the brain can be involved in cerebral infarction; however, pontine infarctions are rare and are generally secondary to occlusive insults or after dissection of an aneurysm. Though not common, these conditions can result in devastating sequelae and significant disability. Scant literature is available regarding pontine infarctions during pregnancy. Here we present a rare case of a pregnant patient who presented with new-onset seizures and was found to have a cerebral pontine infarction on imaging. The purpose of this article is to summarize existing data regarding the incidence, risk factors, and potential etiologies, as well as treatment strategies for pontine infarctions during pregnancy. Keywords: Cerebral infarction, Pontine infarction, Pregnancy, Gestational